(3GdefgGL GdMfja aj GSeg JYGdi GddWjas ((3CMeO ehdhO Hf eMeO Hf dYeQ GdJGbGWi s)
(3ChdgG (B:s
(3hHYO agPg fHPg dWjaI ai eYfi GSeg JYGdi (B" (3GddWja (B" (3heG bjd ajg ef GdNhGU hGdJUQjQa , hMUQJ Pdc ai ebOeI hHGHjf hNGJeI s
(3BNQgG (B:s
(3Ke jUdi Ydi GdfHi ahdG hYOOkG , hjNJe OYGAI HBejf Ke jUdi QcYJjf eY eQGYGg eG SHb ef GdTQhW hGdCOH , hgPG LGA ai LejY GdCSeGA hdjcf gPG BNQ eG bUOJ LeYg ajg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3MhGagG eJBcdIs
(3hHYV GdYHGQGJ ajgG HGdMeQIs
(3fSNI eUMMI cJHgG fGSNgG dTjNI heQHjg NWQ Hf GdWGdH dYHjO GdLefi s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs